Factors Affecting Nurse Response Time in Handling Traffic Accident Cases in the Emergency Room of District Semarang - Ayu Fina Lestari; Septo Pawelas Arso; Sutopo Patria Jati (Green Publisher Indonesia, 2024)
The emergency department (ED) of a hospital plays a crucial role in managing emergency cases, including initial examination, resuscitation, and stabilization. Timely and precise intervention in the ED is vital, as prompt treatment can reduce mortality by up to 30%. Conversely, delayed response times can lead to permanent disability or death. An emergency is defined as a clinical situation requiring immediate medical action to save lives and prevent disability. In this study, the majority of patients (over 80%) admitted to the ED were victims of traffic accidents, including motorcycle, car, bicycle, and pedestrian incidents, while the remainder involved falls, impacts with objects, and violence-related injuries. This research utilized a total sampling method, where all members of the population were included as samples. The study results indicate that training significantly improves nurse response times in handling traffic accident cases in the ED of Semarang Regency Hospital. Additionally, triage skills have a significant positive impact on nurse response times, as does the work environment. However, the workload was found to have an insignificant positive effect on response times. These findings underscore the importance of training, triage proficiency, and a supportive work environment in enhancing nurse response times in emergency situations, particularly in traffic accident cases. Further research may explore additional factors influencing response times and the potential for improving patient outcomes in emergency settings.